E-Paper Analisa sebagai Media Peningkatan Antusiasme Pemilih Pemula - Saragi, Yosafat Steven; Khairullah, Khairullah (Universitas Medan Area, 2025)
This study aims to describe the role of E-Paper Analisa as a medium in enhancing the enthusiasm and participation of first-time voters in general elections. The research employed a qualitative descriptive approach using in-depth interviews with several first-time voters who actively access E-Paper Analisa. Data were analyzed thematically to explore the experiences, perceptions, and interpretations of informants regarding the political content provided by the platform. The findings reveal that easy accessibility through digital devices, the credibility of information sources, and the relevance of political issues presented in an up-to-date manner contribute significantly to strengthening the political efficacy of young voters. This impact is reflected in their growing self-confidence, interest, and political awareness, as well as their readiness to participate in elections. Beyond serving as an information medium, E-Paper Analisa plays a vital role in shaping political literacy among the younger generation by delivering political discourse that is accessible and contextual. The conclusion highlights that E-Paper Analisa is not merely a news dissemination channel but also an effective instrument of political literacy that fosters critical participation and enthusiasm among first-time voters. These findings enrich the literature on the relationship between digital media and political participation, and further studies are recommended to examine more deeply the influence of online media on the political behavior of young voters.